Peran Dan Kontribusi Wanita Tani Kelapa Sawit Terhadap Pendapatan Keluarga Di Desa Bunga Mas - Sentri Anggraini; Yossie Yumiati; Ana Nurmalia (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Female farmers are women who are actively involved in agricultural activities and contribute to the family economy. This study aims to analyze the role and contribution of female farmers to family income in oil palm farming in Bunga Mas Village, Kikim Timur District, Lahat Regency. The method used is descriptive with quantitative and qualitative approaches, involving 61 respondents through a census method. The results show that female farmers play a role in land clearing (26.23%), collecting loose fruit (36.07%), fertilizing (18.03%), and spraying (19.67%). The contribution of female farmers' income reached 53.18% with an average of IDR 3,123,214 per month. These findings confirm that female farmers play a significant role in improving the welfare and economic resilience of oil palm farming families.